Pengaruh Celebrity Endorser Terhadap Keputusan Pembelian Skincare Scarlett Whitening Di Universitas HKBP Nommensen Medan - Siringo-ringo, Honi Yunika Sandella; Sihombing, Natalia E.; Degodona, L. Primawati (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
This study aims to determine the Influence of Celebrity Endorsers on Purchasing Decisions for Scarlett Whitening Skincare at HKBP Nommensen University, Medan. The influence given by celebrity endorsers in this study was measured through Attractiveness, Trustworthiness, and Expertise. The type of research used in this study is a quantitative approach. The population in this study were all HKBP Nommensen University Students in Medan who had or were using Scarlett Whitening skincare products. Based on the Slovin formula, the sample used in this study was 98 respondents. The sampling technique in this study was by using a non-probability sampling technique with Purposive sampling. From the results of this study, it can be concluded that Celebrity Endorsers influence the Purchasing Decision for Scarlett Whitening Skincare at HKBP Nommensen University, Medan.